1976
DOI: 10.3758/bf03213216
|View full text |Cite
|
Sign up to set email alerts
|

Recall memory for visually presented chess positions

Abstract: A series of three experiments replicated and extended earlier research reported by Chase and Simon (1973), de Groot (1965), and Charness (Note 1). The first experiment demonstrated that the relationship between memory for chess positions and chess skill varies directly with the amount of chess-specific information in the stimulus display. The second experiment employed tachistoscopic displays to incrementally "build" tournament chess positions by meaningful or nonmeaningful chunks and demonstrated that meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 13 publications
2
80
0
2
Order By: Relevance
“…Similar results were found by Frey and Adesman (1976), who used a different interfering task. Their subjects were confronted with two positions, presented in sequence for 8 s each, after which they had to count backward and aloud for 3 or 30 s. Finally, they had to reconstruct the first or the second position, without knowledge of which one was going to be chosen.…”
Section: Stm Capacity and Ltm Encoding Interference Studiessupporting
confidence: 78%
See 3 more Smart Citations
“…Similar results were found by Frey and Adesman (1976), who used a different interfering task. Their subjects were confronted with two positions, presented in sequence for 8 s each, after which they had to count backward and aloud for 3 or 30 s. Finally, they had to reconstruct the first or the second position, without knowledge of which one was going to be chosen.…”
Section: Stm Capacity and Ltm Encoding Interference Studiessupporting
confidence: 78%
“…It has been shown that pieces presented at a rapid rate (about 2 s per piece) are better retained when they are presented according to the chunk relations proposed by Chase and Simon (1973a) than when they are presented by columns or randomly; this result holds for both verbal and visual presentation (Charness, 1974;Frey and Adesman 1976). Interestingly, chunk presentation yielded better recall than presentation of the entire position for the same total time (Frey & Adesman 1976).…”
Section: Direct Evidence For Chunksmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, in contrast to the usual assumptions about short-term memory, chess masters are relatively insensitive to interference tasks (Charness, 1976;Frey & Adesman, 1976) and can recall several boards that have been presented successively (Cooke, Atlas, Lane & Berger, 1993;Gobet & Simon, 1996a). In addition, Chase and Ericsson (1982) and Staszewski (1990) have shown that highly trained subjects can memorize up to 100 digits dictated at a brisk rate (1 second per digit).…”
Section: Template Theory and Memory Chunksmentioning
confidence: 99%